Moderate Fields, Maximum Potential: Achieving High Records with Temperature-Stable Energy Storage in Lead-Free BNT-Based Ceramics - Shi, Wenjing; Zhang, Leiyang; Jing, Ruiyi; Huang, Yunyao; Chen, Fukang; Shur, Vladimir; Wei, Xiaoyong; Liu, Gang; Du, Hongliang; Jin, Li (Nano-Micro Letters, 2024)
The increasing awareness of environmental concerns has prompted a surge in the exploration of lead-free, high-power ceramic capacitors. Ongoing efforts to develop lead-free dielectric ceramics with exceptional energy-storage performance (ESP) have predominantly relied on multi-component composite strategies, often accomplished under ultrahigh electric fields. However, this approach poses challenges in insulation and system downsizing due to the necessary working voltage under such conditions. Despite extensive study, bulk ceramics of (Bi0.5Na0.5)TiO3 (BNT), a prominent lead-free dielectric ceramic family, have seldom achieved a recoverable energy-storage (ES) density (Wrec) exceeding 7 J cm−3. This study introduces a novel approach to attain ceramic capacitors with high ESP under moderate electric fields by regulating permittivity based on a linear dielectric model, enhancing insulation quality, and engineering domain structures through chemical formula optimization. The incorporation of SrTiO3 (ST) into the BNT matrix is revealed to reduce the dielectric constant, while the addition of Bi(Mg2/3Nb1/3)O3 (BMN) aids in maintaining polarization. Additionally, the study elucidates the methodology to achieve high ESP at moderate electric fields ranging from 300 to 500 kV cm−1. In our optimized composition, 0.5(Bi0.5Na0.4K0.1)TiO3–0.5(2/3ST-1/3BMN) (B-0.5SB) ceramics, we achieved a Wrec of 7.19 J cm−3 with an efficiency of 93.8% at 460 kV cm−1. Impressively, the B-0.5SB ceramics exhibit remarkable thermal stability between 30 and 140 °C under 365 kV cm−1, maintaining a Wrec exceeding 5 J cm−3. This study not only establishes the B-0.5SB ceramics as promising candidates for ES materials but also demonstrates the feasibility of optimizing ESP by modifying the dielectric constant under specific electric field conditions. Simultaneously, it provides valuable insights for the future design of ceramic capacitors with high ESP under constraints of limited electric field. Highlights: 1 Achieving ultrahigh energy-storage density (7.19 J cm−3) and outstanding storage efficiency (93.8%) at 460 kV cm−1 in BNT-based relaxor ferroelectric ceramics under a moderate electric field. 2 Superior energy-storage performance accomplished through meticulous regulation of permittivity, enhancement of insulation quality, and strategic domain engineering via chemical formula optimization. 3 The intricate structure–property relationship elucidated with precision using high-resolution transmission electron microscopy.